موسيقى الشعر العربي الحديث برؤى النقاد والشعراء - ولي فتاح يحيى; قيس إسماعيل سرّاء (Journal of College of Education, 2019)
Poetry is an essential element - in poetry in general and in modern Arabic poetry in particular - in stimulating the poetic experience. It is more self-explanatory and more relevant to the mind. Hair is a balanced, hollowed word that indicates the meaning of poetry being swayed by prose and rhyme. The critics and the modern poets - as well as the interested ones - differed very much in their visions of modern Arabic poetry. Some of them called it the poetic rhythm, without specifying it precisely, so that it would not be included in the music of poetry. Limited to hair only; distinguishing between weighted rhythm and uncontrolled rhythm. While a section focused on the